Pengaruh Thin Capitalization, Transfer Pricing Dan Capital Intensity Terhadap Penghindaran Pajak Pada Perusahaan Manufaktur - Aditia Prayoga (Journal of Business and Economics (JBE) UPI YPTK, 2019)
This study aims to determine the effect of thin capitalization, transfer pricing and capital intensity on tax avoidance. Thin capitalization, transfer pricing and capital intensity are used as independent variables and tax avoidance is used as the dependent variable. This research was conducted on manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2015-2019. The data is obtained by accessing the Indonesia Stock Exchange page. The method of determining the sample in this study used the purposive sampling method so that the number of samples obtained was 62 companies. The data in this study were analyzed using panel data regression analysis technique using Eviews 9. The results showed that simultaneously thin capitalization, transfer pricing and capital intensity had a significant effect on tax avoidance. While partially thin capitalization has no significant effect on tax avoidance, transfer pricing and capital intensity have a significant effect on tax avoidance